2014
DOI: 10.1021/jp507644z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Relationships between the Crystal Structure and 31P Isotropic Chemical Shifts in Calcined Aluminophosphates

Abstract: Solid-state NMR spectra have historically been assigned using simple relationships between NMR parameters, e.g., the isotropic chemical shift, and aspects of the local structure of the material in question, e.g., bond angles or lengths. Density functional theory (DFT) calculations have effectively superseded these relationships in many cases, owing to the accuracy of the NMR parameters typically able to be calculated. However, the computational time required for DFT calculations may still be prohibitive, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 73 publications
5
39
3
Order By: Relevance
“…This relationship is different from that reported for calcined AlPOs, 54 but similar to that derived from computational results as discussed in the Supporting Information (S9).…”
Section: Solid-state Nmr Spectroscopycontrasting
confidence: 81%
See 2 more Smart Citations
“…This relationship is different from that reported for calcined AlPOs, 54 but similar to that derived from computational results as discussed in the Supporting Information (S9).…”
Section: Solid-state Nmr Spectroscopycontrasting
confidence: 81%
“…54 The work presented here demonstrates an extension of our earlier work, focused on calcined AlPOs, to materials containing disordered SDAs and frameworkbound anions, suggesting that the method may be more generally applicable to AlPOs containing guest molecules; further investigation of this is ongoing.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Approaches that have been used successfully in NMR studies include quench-cooling of MD simulations of molten solids, 65 as well as approaches that avoid the need for large-scale DFT calculations, such as training neural networks to predict chemical shifts in glasses 66 or deriving empirical correlations from related compounds. 67,68 In contrast to "static disorder," dynamics tend to average NMR parameters, and so, depending on the time scale of the dynamics, will narrow rather than broaden NMR line shapes. This is illustrated in Fig.…”
Section: Beyond Periodicitymentioning
confidence: 99%
“…In a continuation of their earlier studies, recently reviewed by the principal authors, Dawson, et al performed a systematic DFT investigation of the solid‐state 31 P NMR isotropic chemical shifts of the local structure of aluminophosphates, capable of providing information on the number of crystallographic phosphorus sites, their relative populations, and the positions of any dopant atoms in the framework. Based on the recently demonstrated simple relationship between the local structure around phosphorus atom (first of all, the mean P─O bond length and P─O─Al bond angle) and calculated at the DFT level 31 P NMR isotropic chemical shift, δ iso , for a series of calcined aluminophosphates, the authors extended this approach to "as‐made" aluminophosphates, illustrated in Figure . It was demonstrated that the presence of the framework‐bound anions and/or guest species within the pores of aluminophosphates could be translated directly to a distortion of the local framework geometry without considering any additional structural parameters.…”
Section: Computation Of 31p Nmr Chemical Shifts: Accuracy Factors Andmentioning
confidence: 99%